Reviews Books. Issue 3 (1st September 2015) - Bye, Joseph; Campbell, Sean; Clarke, Dominic; Copman, Wiebe; Gant, Sophia; Garza, Oscar; Holmes, Brent; Incrucio, Mars; Jarman, Cody; King, Justin Ray Jonathan; Martin, Richard F.; Siddiqui, Afra; et al.
A Corpus of CorpsesThe Philosophy of Tim Burton, Jennifer L. McMahon (ed.), (2014)Lexington: University Press of Kentucky, 328 pp., ISBN: 9780813144627 (hbk), 40.00The Politics of Hollywood Cinema: Popular Film and Contemporary Political Theory, Richard Rushton, (2013)Basingstoke, Hampshire: Palgrave Macmillan, 248 pp., ISBN: 9780230244580 (hbk), 90.00Boyhood: Twelve Years on Film, Matt Lankes, (2014)Austin: University of Texas Press, 200 pp., ISBN: 9781477305416 (hbk), 50.00Beyond the Looking Glass: Narcissism and Female Stardom in Studio-Era Hollywood, Ana Salzberg, (2014)New York: Berghahn Books, 206 pp., ISBN: 9781782383994 (hbk), 90.00Indie 2.0: Change and Continuity in Contemporary American Indie Film, Geoff King, (2014)New York: Columbia University Press, 288 pp., ISBN: 9780231167949 (hbk), 90, ISBN: 9780231167956 (pbk), 30, ISBN: 9780231537896 (e-book), 29.99Joss Whedon, A Creative Portrait: From Buffy the Vampire Slayer to Marvel's The Avengers, David Lavery, (2014)New York: IB Tauris, 278 pp., ISBN-13: 9781848850309 (pbk), 18.00Parallel Lines: Post 9/11 American Cinema, Guy Westwell, (2014)New York: Wallflower Press, 208 pp., ISBN: 9780231172035 (pbk), 27.00Blossoms & Blood: Postmodern Media Culture and the Films of Paul Thomas Anderson, Jason Sperb, (2013)Austin: University of Texas Press, 296pp., ISBN: 029275289X (hbk), 60.00The Encyclopedia of Film Composers, Thomas S. Hischak, (2015)New York: Rowman & Littlefield, 819 pp., ISBN: 1442245492 (hbk), 95.00From Chariots of Fire to The King's Speech: Writing Biopics and Docudramas, Alan Rosenthal, (2014)Carbondale: Southern Illinois University Press, 197 pp., ISBN: 9780809332984 (pbk), 33.00, ISBN: 0809332981 (pbk), 33.00, ISBN: 9780809332991 (e-book), 33.00, ISBN: 080933299X (e-book), 33.00Film Restoration: The Culture and Science of Audiovisual Heritage, Leo Enticknap, (2013)New York: Palgrave Macmillan, 256 pp., ISBN: 9780230230439 (hbk), 85.00Death in Classic and Contemporary Film: Fade to Black, Daniel Sullivan and Jeff Greenberg (eds.), (2013)New York: Palgrave Macmillan, 276 pp., ISBN: 9781137276889 (hbk), 85.14Shooting the Moon, Brian Willems, (2015)Alresford: Zero Books, 221 pp., ISBN: 9781782798484 (pbk), 24.95The Philosophy of Michael Mann, Steven Sanders, Aeon J. Skoble, and R. Barton Palmer (eds.), (2014)Lexington: University Press of Kentucky, 284 pp. ISBN: 9780813144719 (hbk), 40.00